A PREDICTIVE VALUE OF EARLY CLINICAL PARAMETERS FOR ABNORMAL BRAIN MRI SCAN IN NEONATES TREATED WITH THERAPEUTIC HYPOTHERMIA: Early clinical indicators of abnormal brain MRI - Hadžimuratović, Emina; Hadžimuratović, Admir; Pokrajac, Danka; Selimović, Amina; Muhasilović, Senad (Sanamed, 2022)
Introduction: Brain MRI scans can predict neurodevelopmental outcomes in neonates treated with therapeutic hypothermia. It is a common clinical practice to perform brain MRI before discharge, but brain MRI scans performed at around four months of age have a better prognostic value for a long-term neurological outcome in asphyxiated neonates.Aim: To identify which of three selected clinical parameters (oral feeding ability, muscle tone, history of seizure) evaluated 10 days after therapeutic hypothermia could predict the primary outcome of an abnormal brain MRI.Methods: We reviewed the medical records of neonates ≥ 36 completed weeks of gestation consecutively treated with therapeutic hypothermia who underwent brain MRI. Clinical parameters on day 10 after therapeutic hypothermia were correlated with brain MRI findings in the first 7-14 days of life. Logic regression analysis was performed using all three covariates of the clinical status, with an abnormal MRI as the primary outcome.Results: Brain MRI was abnormal in 42 (51.85 %) neonates with the following distribution of brain injury patterns: abnormal signal in the basal nuclei in 6, an abnormal signal in the cortex in 16, an abnormal signal both in the cortex and basal nuclei in 20 neonates. Out of three analyzed clinical parameters, feeding difficulty (P < 0.001, OR 8.3, 95% CI 2.9 - 28.9) and a history of seizures (P < 0.001, OR 11.95, 95% CI 3 - 44.5) were significantly associated with an abnormal MRI. Conclusion: Neonates who were capable of full oral feeding by day 10 after therapeutic hypothermia and had no history of seizures were unlikely to have an abnormal MRI. This may be used in selective planning of pre-discharge MRI in asphyxiated neonates.
Keywords: therapeutic hypothermia; clinical parameters; feeding difficulties; seizures; brain MRI